2022
DOI: 10.7759/cureus.25589
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Blue Rubber Bleb Nevus Syndrome With Kasabach-Merritt Syndrome and Heart Failure

Abstract: A 48-year-old Mongolian man developed bilateral leg edema after suffering from a fever for three months. He lost his appetite, and the edema gradually spread from the legs, becoming systemic. In addition, he had difficulty in moving. He had a history of being diagnosed with numerous venous malformations and Kasabach-Merritt syndrome when he was a child. On arrival, he had numerous venous malformations over pale skin, edema at each extremity, and anemic conjunctiva. Chest roentgen showed bilateral pleural effus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The occurrence of BRBNS with KMP is extremely rare. Jitsuiki et al (7) reported a similar case in a Japanese study. At present, no similar report from China has been found.…”
Section: Introductionmentioning
confidence: 80%
“…The occurrence of BRBNS with KMP is extremely rare. Jitsuiki et al (7) reported a similar case in a Japanese study. At present, no similar report from China has been found.…”
Section: Introductionmentioning
confidence: 80%